Effect of Thickness Stretching on Bending and Free Vibration Behaviors of Functionally Graded Graphene Reinforced Composite Plates - Zhuangzhuang Wang; Liansheng Ma (Applied Sciences, 2021)
The focus of this paper is the effect of thickness stretching on the static and dynamic behaviors of functionally graded graphene reinforced composite (FG-GRC) plates. The bending and free vibration behaviors of FG-GRC plates under simply supported conditions are studied based on two plate theories, with or without taking into account the thickness stretching effect, respectively, and the effect of thickness stretching on FG-GRC plates is analyzed by comparing the calculated results of the two types of plate theories. The properties of composite materials are estimated by the modified Halpin-Tsai model and rule of mixture, Hamilton’s principle is used to construct its governing equation, and the Navier solution method is used to find the closed solution. The numerical results show that the effect of thickness stretching depends mainly on the transverse anisotropy of the FG-GRC plates, and the FG-GRC plates are most significantly affected by the thickness stretching when the graphene nanoplatelets (GPLs) are asymmetrically distributed, and the effect of thickness stretching tends to increase as the total number of layers and the weight fraction of GPLs increase.